Une ouverture sur le monde: la nouvelle politique étrangère canadienne du gouvernement Chrétien - Kirton, John (Études internationales, 1996)
When the Liberal government of Jean Chrétien was elected with its strong majority mandate in October 1993, there were few prospects of any substantial change in the long established liberal-internationalist foundations of Canadian foreign policy. As the government moves into the second half of its mandate, however, it is clear that important change has taken place. Both Pearsonian internationalism and Trudeauvian nationalism have been swept away as the central elements in Canadian foreign policy, in favour of an assertive globalism. Although many of these changes were introduced by the Mulroney government and flourished in its later years, under Chrétien the transformation has acquired new strength and speed. Yet because it is largely a reactive rather than strategic process, devoid of the vision which Prime Minister Pierre Trudeau brought into office, there mil continue to be periodic]'allures, difficult adjustments and opportunities missed.